The use of prosthetic mesh in adult inguinal hernia repair - Majeed, Laith Qauis; Surriah, Mohammed Hillu; Bakkour, Amine Mohammed; Saaid, Ayaad Makki (International Surgery Journal, 2019)
Background: An abdominal wall hernia is a protrusion of a viscus or part of a viscus through an abnormal opening in the wall of the abdominal cavity. Different approaches have been described in regards to management and repair of hernia. The present study aims at showing the rate of frequency to use the prosthetic mesh versus classical repair in adult inguinal hernia. Methods: A retrospective study lasted from October 2014 to July 2018 in Al-Karama Teaching Hospital. The study Samples consist of 315 patients with inguinal hernia, the age group (20-70) years old they were diagnosed according to clinical examination. There are 76 patients operated on using mesh technique (tension free). Results: All patients in our series were male, with age group (20-70) years. However, the inguinal hernia more frequent with increase age. In age groups; (40-49) was 25 patients (32.89%). The indirect inguinal hernias are most common in the young 65% whereas direct hernias are most common in the old. In our series sixty-one (80.26%) patients with indirect inguinal hernias, eleven (11.82%) patients with direct hernias and six (5.263%) patients with pantaloon type. Conclusions: The frequent uses of mesh in inguinal hernioplasty increasing with age. Tension –free hernioplasty is technically simple surgical operation, which can be used to repair any groin hernia. The use of mesh patch with or without plug is technically easier to work than the classical methods and far simple to secure to surrounding tissues.